Influence of temperature on cyclic fatigue resistance of nickel-titanium reciprocating files / Tan Tat Wah - Tan, Tat Wah (2019)
Aim: To evaluate cyclic fatigue resistance of Reciproc Blue R25 and WaveOne Gold Primary at 20°C and 35°C. Material & Methods: Cyclic fatigue resistance of rotary nickel-titanium instrument, Reciproc Blue R25 (VDW Dental, Munich, Germany) and WaveOne Gold Primary (Dentsply Maillefer, Baillagues, Switzerland) files were tested at 20°C and 35°C in a stainless steel artificial canal, with 60° angle of curvature and curvature radius of 5 mm. The instruments reciprocated freely within the stainless steel canal until fracture. Time between commencement of the rotation and file breakage was recorded. The length of the fractured fragments were noted. Two-way ANOVA was used to compare the length of the fractured fragments, the time to failure (in seconds) of same system between temperatures, and the time to failure of different system at the same temperature. The level of significance was set at α=0.01. Results: There were no statistically significant differences among the fracture length of separated instruments (p>0.05). Reciproc Blue R25 showed a statistically significant reduction in fatigue life at 35°C compared with 20°C (p<0.001) whereas WaveOne Gold Primary had no significant difference in cyclic fatigue resistance between the 2 temperatures tested (p>0.05), Reciproc Blue R25 instruments exhibited a significantly higher resistance to cyclic fatigue than WaveOne Gold Primary instruments at both 20°C and 35°C (p<0.001). Conclusion: Cyclic fatigue resistance of Reciproc Blue is significantly reduced when the environmental temperature is increased from 20°C to 35°C. However, increasing environmental temperature from 20°C to 35°C does not affect the cyclic fatigue iv resistance of WaveOne Gold. Reciproc Blue showed significant better cyclic fatigue resistance than WaveOne Gold at both 20°C and 35°C. Keywords: Cyclic fatigue resistance, nickel-titanium, temperature, reciprocating